Minimization of Heat Losses in District Heating Networks by Optimizing their Configuration - Skochko V.; Solonnikov V.; Pohosov O.; Haba K.; Kulinko Ye.; Koziachyna B. (Problems of the Regional Energetics, 2024)
The objective of this work is to elucidate the mathematical foundations for optimizing the con-figuration of district heating system networks. Existing and most effective approaches to opti-mizing thermal networks based on minimizing heat losses were analysed, and principles and cor-responding mathematical tools were proposed to account for objective technical constraints im-posed on these district heating networks by regulatory requirements, both at the technological and urban planning levels. The goal is achieved by solving the problems of modeling the coor-dinates of nodes and the lengths of sections of thermal networks using instrumental means to determine the most rational positions of the branching nodes in terms of their coordinates to identify economically viable directions for laying each fragment of the corresponding networks. To make the proposed approach to optimizing thermal networks practical, additional mathemati-cal tools must be introduced to account for specific urban planning conditions and constraints imposed on heating systems, which must be considered in the design process. The most im-portant results are the obtained mathematical model of the district heating network, which allows for considering the actual technical conditions for connection to the networks and urban plan-ning conditions and constraints. The significance of the results obtained is that the application of the developed algorithm allows not only to reduce the total heat losses during the transportation of the heat carrier from heat sources to consumers but also, as a consequence, to increase the energy efficiency level of the entire heating system, reduce primary energy costs, and green-house gas emissions.